Development studies entering a cul-de-sac? Reflections on development studies as an academic discipline: A historical appraisal - Ong, Puay Liu; Sarmila Md Sum, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
The “fate of development studies” in the context of the dominant thinking on development as propagated by development theorists was one of the main themes highlighted in the 5th International Malaysian Studies Conference (MSC5).1 Indeed, the MSC5 convenors evoke the call for a reflection on the implications for and the future of development studies in Malaysia. Reflection on the fate and future of development studies in Malaysia requires us, in particular, to understand how development studies has been understood as an academic discipline and implemented by institutions of higher learning. This article undertakes to do a historical appraisal of development studies as an academic discipline under the guidance of the following questions: (i) How development studies emerge as a (serious) academic discipline in institutions of higher learning; (ii) How these institutions of higher learning define “development” and “development studies”; and (iii) What are their objectives/rationale, methodology and scope? Through this historical appraisal, this article hopes to configurate a model of development studies that incorporates not only the substantive components (interdisciplinary subject matter) but also the praxis component (‘doing’ development through for example, immersion and advocacy) in order to make development studies a socially responsible and relevant field in development process and planning